Visual commentary on unseen characters in response to How to Pronounce Knife - Blaak, Rachel (My University, 2022)
“Mary believed there were two kinds of people in the world. There were those that were seen and those who were not. Mary considered herself one of the latter.” Many characters in How to Pronounce Knife, by Souvankham Thammavongsa, can be considered ‘unseen.’ Despite their invisibility, each short story gives its characters the chance to be seen by the reader and have their voice heard. It is essential to recognize the importance of their final thoughts and actions in their stories because their impact is more substantial than anything their loud counterparts have done or said. This postcard series highlights the importance of what the ‘unseen’ characters are thinking, shown through found poetry. The imagery being used is highlighting specific moments in each story. These characters from Slingshot, The School Bus Driver and The Gas Station are shown through the use of black and white. They are more withdrawn characters but still interesting, so the postcards rely more heavily on texture and details to depict their situation. By using found poetry, the viewer can better understand the progression and development of each character. It highlights ‘unseen’ characters, blocking the louder characters the same way they are depicted in their stories.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta, and at the MacEwan Book of the Year Project.
Keywords: MacEwan Book of the Year; How to Pronounce Knife; Souvankham Thammavongsa; book design